Analisis Kualitas Layanan Situs Kiostix.com Terhadap Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Ninscha Adisti Oktivianet; Ari Kusyanti; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Kiostix.com is one of many e-Commerce that served service to customer with giving an information and do any transaction for selling and buying event ticket that ongoing in Indonesia surrounding areas. A few months ago, in the end of 2016 precisely kiostix.com had a problem with their capability of giving a service to customer with their website. That problem is our discussion in this research with goals to discover the website quality of kiostix.com which will be connected to customer satisfaction. This research use webqual 4.0 as a methodology that has three variables to measuring website quality, which is usability, information quality, and service interaction quality. This research use questionnaire to gather all of data that from respondents, the respondents in this research is the person who had used kiostix.com to do any transaction, the total data is 61 respondents. This research had been test with multiple linear regression. The result is there are only two variables that had a significant relation toward customer satisfaction, usability and service interaction quality, but service interaction variable itself had given a negative effect for customer satisfaction grade. Therefore, all of those variable had given an impact for customer satisfaction if it all gather.